A Comparison of Standard One-Step DDA Circular Interpolators with a New Cheap Two-Step Algorithm. (20th January 2014) - Moroz, Leonid; Cieśliński, Jan L.; Stakhiv, Marta; Maksymovych, Volodymyr
Abstract : We present and study existing digital differential analyzer (DDA) algorithms for circle generation, including an improved two-step DDA algorithm which can be implemented solely in terms of elementary shifts, addition, and subtraction.